A novel space hybrid meshing technique combined with Laguerre polynomial to solve TD-EFIE. Issue 9 (13th June 2021) - Khaled, Auns; Omri, Dorsaf; Aguili, Taoufik
Abstract : In this paper, we have developed a system of Time Domain Electric Field Integral Equation (TD-EFIE) for the resolution of a scattering electromagnetic problem by various shapes illuminated by an incident transient wave. The solvability of the TD-EFIE system is based on the Time Domain Method of Moments (TD-MoM) using Galerkin's method in space and time domains. In time domain, a linear combination of Laguerre functions is used as temporal basis functions. In order to approximate the unknown space variation of the transient current, we develop a novel space hybrid basis functions derived from the Rao-Wilton-Glisson function. The elaborated hybrid mesh technique using hexagonal and triangular mesh is applied for various analyzed structures: regular grid for planar structures and irregular grid for curved structures. The validity, the efficiency and the precision of developed meshing techniques are presented and discussed.